2008
DOI: 10.1080/14622200802087556
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with rapid transition to tobacco dependence in youth

Abstract: Epidemiologic data suggests the smoking trajectory for some adolescents escalates rapidly and that tobacco dependence can develop quickly after initiation. In this study, we examine variation in cigarette consumption and individual characteristics associated with the rapid development of tobacco dependence, focusing particularly on the 24-month interval after tobacco initiation. The analysis is based on public use data files of the National Household Survey on Drug Abuse conducted in 1994-1996. Representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Participants displaying a ‘Telescoped use’ trajectory did not report frequent use of any substance until the last assessment. Previous studies have reported accelerated progressions from the onset of alcohol ( Jackson, 2010 ), tobacco ( Storr, 2008 ) or marijuana use ( Derefinko et al, 2016 ) to their abuse or dependence. However, evidence regarding concurrent use of different substances is still scarce and only exists among adults ( Lewis, Hoffman, & Nixon, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants displaying a ‘Telescoped use’ trajectory did not report frequent use of any substance until the last assessment. Previous studies have reported accelerated progressions from the onset of alcohol ( Jackson, 2010 ), tobacco ( Storr, 2008 ) or marijuana use ( Derefinko et al, 2016 ) to their abuse or dependence. However, evidence regarding concurrent use of different substances is still scarce and only exists among adults ( Lewis, Hoffman, & Nixon, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using data obtained from one such tool, the Youth Self-Report (YSR) developed by Achenbach, 41 find emotional and/or behavioral problems to be associated with substance use. [42][43][44] Problem behaviors have also been associated with a rapid development of nicotine dependence among youth who recently initiated smoking 45 and with both single and multiple SUDs in early adulthood. 46 It takes time and resources to assess a variety of psychiatric and SUDs.…”
Section: Assessment Issuesmentioning
confidence: 99%
“…Additionally, adolescents, particularly female adolescents, seem to progress more rapidly to nicotine dependence after initial use than adults (SAMHSA 2007) and show higher rates of dependence, even though adolescents report smoking fewer cigarettes than do adults (Tanski et al 2004; Storr 2008). Despite these findings, and the fact that smoking generally begins during adolescence, most animal studies have focused on adult males (but see McQuown et al 2007; Shram et al 2008a; b; Levin et al 2007; Adriani et al 2003).…”
Section: Introductionmentioning
confidence: 99%